2006
DOI: 10.1002/ange.200504417
|View full text |Cite
|
Sign up to set email alerts
|

Precedent and Theory Unite in the Hypothesis of a Highly Selective Fluoride Receptor

Abstract: Platz für was Kleines: Für mehrere [1,3,5]Cyclophan‐basierte Rezeptoren, die Triazin‐, Cyanursäure‐ oder Boroxinringe enthalten, wird vorhergesagt, dass sie Fluoridionen mit einer Kombination aus Anion‐π‐Wechselwirkungen und Ionenpaar‐verstärkten H‐Brückenbindungen fest komplexieren und zugleich das Chloridion wegen seiner Größe ausschließen. Die berechnete Struktur des Triazinkäfigs mit eingeschlossenem Fluoridion ist gezeigt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…In the theoretical treatment of this receptor, the complexation of fluoride ion was shown to benefit from intrinsically stronger π⋅⋅⋅X − ⋅⋅⋅π and + NH⋅⋅⋅X − interactions than for chloride. This difference, in addition to acute steric issues associated with accommodating the larger chloride anion in the cavity, led to a calculated 23.5 kcal mol −1 difference in binding energy between the two halides in aqueous solution 9. Herein, we present the proof of principle behind the design of 2 .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the theoretical treatment of this receptor, the complexation of fluoride ion was shown to benefit from intrinsically stronger π⋅⋅⋅X − ⋅⋅⋅π and + NH⋅⋅⋅X − interactions than for chloride. This difference, in addition to acute steric issues associated with accommodating the larger chloride anion in the cavity, led to a calculated 23.5 kcal mol −1 difference in binding energy between the two halides in aqueous solution 9. Herein, we present the proof of principle behind the design of 2 .…”
Section: Methodsmentioning
confidence: 97%
“…We ourselves described a hypothetical series of purpose‐designed fluoride receptors that took advantage of the cylindrophane effect, that is, the high conformational stability and limited vertical flexibility of [1,3,5]cyclophanes bridged by chains with odd numbers of atoms, such as 1 (Scheme ). While 1 has been shown to be a selective silver(I) and copper(I) host,8 it was demonstrated that an inversion of its electronic character from electron‐rich to electron‐poor, such as in 2 , would produce an anion host 9. In the theoretical treatment of this receptor, the complexation of fluoride ion was shown to benefit from intrinsically stronger π⋅⋅⋅X − ⋅⋅⋅π and + NH⋅⋅⋅X − interactions than for chloride.…”
Section: Methodsmentioning
confidence: 99%
“…They found that fluoride forms a covalent bond with an aryl carbon, while chloride and azide exhibit a non-covalent minimum with the anion located above the ring. In later work, Mascal [84] used B3LYP to investigate complexes of s-triazine, cyanuric acid, and boroxine ring with fluoride and chloride, finding that the complexes with fluoride are more favorable than the corresponding Cl À complexes.…”
Section: Anion/p Interactionsmentioning
confidence: 98%
“…Numerous experimental and theoretical research findings have demonstrated that the anion-p interaction is of importance in molecular recognition and transmembrane anion transport. [8][9][10][11][12][13][14][15] It hasb een revealed that the anion-p interaction is mainly caused by electrostatic and anion-induced polarization interactions. [16][17][18] Recently,m uch attention has been focusedo nt etrel bonding (TB) due to its roles in chemical reactions, crystal engineering, and biological systems.…”
Section: Introductionmentioning
confidence: 99%